Осінь 1919 р.: доля об'єднаного фронту - Солдатенко, В.Ф. (Український історичний журнал, 2009)
У статті зроблено спробу з’ясувати причини суперечностей, що лежали в основі орієнтацій і, відповідно, поведінки двох головних складових об’єднаного українського фронту 1919 р. – Дієвої армії УНР і Української галицької армії ЗОУНР. Аналізується мотивація процесу переходу УГА в табір денікінських Збройних сил Півдня Росії і тенденції до зближення з Польщею, що домінували в оточенні С.Петлюри. Полярність обраних політичних курсів зумовила руйнацію об’єднаного фронту, що оформився у ході реалізації Акту злуки. The article makes an attempt to find out the reasons for contradictions that underlay the orientations and thus behavior of two main components of united Ukrainian front of 1919 – Active Army of Ukrainian People's Republic and Ukrainian Halych Army of Western Region of Ukrainian People's Republic. The author analyzes motivation of the process of passing of Ukrainian Halych Army into encampment of Denikin Armed Forces of the South of Russia and tendency towards closer relations with Poland that dominated in S.Petliura's surrounding. Polarity of the chosen political courses caused the destruction of the united front, which was formed during realization of Union Act.